The disintegrated theory of consciousness: Sleep, waking, and meta-awareness. (23rd March 2022) - Zadra, Antonio; Levitin, Daniel J.
Abstract: The study of sleep and wakefulness can inform debates about the nature of consciousness. We argue that sleep and wakefulness fall along a multidimensional continuum and that inconsistencies and paradoxes with the accounts put forth by Merker et al. and Tononi can be understood in terms of a pervasive false dichotomy between these two states.